Sobre la indeterminación ética del procedimiento kantiano de universalización y su relación con el «principio supremo de la doctrina de la virtud» - Marey, Macarena (2011)
This article explores the ethical indetermination of the universalisation procedure described in the categorical imperative formula of the universal law (GMS, AA iv 421), from the perspective of the definitive form of Kant’s ethics expounded in the Metaphysics of Morals.